Low-Volume (0.3 mL/kg) Ropivacaine 0.5% for a Quadratus Lumborum Block in Cats Undergoing Ovariectomy: A Randomized Study - Chiara Di Franco; Camilla Cozzani; Iacopo Vannozzi; Angela Briganti (Veterinary Sciences, 2025)
Elective surgical ovariectomy is one of the most common surgical procedures in veterinary medicine [...]